Tim x biết \(\left(2x-1\right)^6=\left(2x-1\right)^8\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(2x-1\right)^6=\left(2x-1\right)^8\)
\(\Leftrightarrow\left(2x-1\right)^6-\left(2x-1\right)^8=0\)
\(\Leftrightarrow\left(2x-1\right)^6\left[1-\left(2x-1\right)^2\right]=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(2x-1\right)^6=0\\1-\left(2x-1\right)^2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}2x=1\\2x-1=1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{2}\\2x=2\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=1\end{cases}}\)
\(1,\left(2x+1\right)\left(x-1\right)-x\left(2x-3\right)+3=0\)
\(\Rightarrow2x^2-2x+x-1-\left(2x^2-3x\right)+3=0\)
\(\Rightarrow2x^2-2x+x-1-2x^2+3x+3=0\)
\(\Rightarrow2x=-2\Rightarrow x=-1\)
\(2,\left(x^2+x-2\right)\left(x^2-x-2\right)-x^2\left(x^2-2\right)+8=0\)
\(\Rightarrow[\left(x^2\right)^2-\left(x-2\right)^2]-x^2\left(x^2-2\right)+8=0\)
\(\Rightarrow x^4-\left(x^2-4x+4\right)-x^4+2x^2+8=0\)
\(\Rightarrow x^4-x^2+4x-4-x^4+2x^2+8=0\)
\(\Rightarrow x^2+4x+4=0\)
\(\Rightarrow\left(x+2\right)^2=0\Rightarrow x=-2\)
\(\left(2x+1\right)^4=\left(2x+1\right)^6\)
\(\Rightarrow\left(2x+1\right)^4=\left(2x+1\right)^4.\left(2x+1\right)^2\)
\(\Rightarrow\left(2x+1\right)^2=\left(2x+1\right)^4:\left(2x+1\right)^4\)
\(\Rightarrow\left(2x+1\right)^2=1\)
\(\Rightarrow\left(2x+1\right)^2=1^2\)
\(\Rightarrow2x+1=1\)
\(\Rightarrow2x=0\)
\(\Rightarrow x=0\)
Vậy \(x=0\)
\(\left(2x+1\right)^4\)\(=\left(2x+1\right)^6\)
\(\Rightarrow\left(2x+1\right)^4\)\(=\left(2x+1\right)^4\)\(.\left(2x+1\right)^2\)
\(\Rightarrow\left(2x+1\right)^2\)\(=\left(2x+1\right)^4\)\(:\left(2x+1\right)^4\)
\(\Rightarrow\)\(\left(2x+1\right)^2\)\(=1^2\)
\(\Rightarrow\)\(2x+1=1\)
\(\Rightarrow2x=0\)
\(\Rightarrow x=0\)
a)(x+3)3-x(3x+1)2+(2x+1)(4x2-2x+1-3x2)=54
\(\Rightarrow\)x3+9x2+27x+27-x(9x2+6x+1)+(2x+1)(x2-2x+1)=54
\(\Rightarrow\)x3+9x2+27x+27-9x3-6x2-x+2x3-4x2+2x+x2-2x+1=54
\(\Rightarrow\)-6x3+26x+28=54
\(\Rightarrow\)-6x3+26x=54-28
\(\Rightarrow\)-6x3+26x=26
\(\Rightarrow\)-6x3+26x-26=0
\(\Rightarrow\)-2(3x3+13x+14)
(2x-1)6=(2x-1)8
=>(2x-1)8-(2x-1)6=0
=>(2x-1)6[(2x-1)2-1]=0
=>(2x-1)6=0
=>x=1/2
và (2x-1)2-1=0
=>(2x-1)2=1
=>2x-1=-1;1
=>x=0;1
vậy x=1/2;0;1